Geografia: Leituras Culturais em Daniel W.Gade - Geralda de Almeida, Maria; JP Ratts, Alecsandro (Terra Livre, 2015)
Maria Geralda de Almeida and Alecsandro JPRatts (eds.). Goiânia: Editora Alternativa. 2003. 287 pp. ISBN 85-88253-19-4Daniel W. Gade